Fault-Tolerant Guidance of Rocket Vertical Landing Phase Based on MPC Framework - Jingqi Li; Yaosong Long; Mao Su; Lei Liu; Bo Wang; Zhongtao Cheng (International Journal of Aerospace Engineering)
For the vertical landing process of reusable rockets, the landing accuracy is likely to be affected by disturbances and faults during flight. In this paper, a fault-tolerant guidance method based on the MPC framework is put forward. First, we propose a piecewise guidance algorithm that combines a trajectory optimization algorithm based on convex optimization with the MPC framework. With the fast trajectory optimization algorithm and the MPC framework that recursively introduces the real-time state, this algorithm forms a robust closed loop. Then, we design an integrated guidance, navigation, and control (GNC) system to enhance the fault tolerance and robustness of the guidance method. Simulation experiments verify that this method is fault-tolerant to various fault conditions including navigation system failures, control system failures, drag coefficient deviations, and atmospheric density deviations. This guidance method is robust enough to overcome disturbances and faults, and it has great potential for online use.